Changing maladaptive beliefs among individuals with coronary heart disease using video information - Ginting, Henndy; Näring, Gérard W. B.; Becker, Eni Sabrine; Tedjokusumo, Pintoko (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2021)
Many individuals with coronary heart disease (CHD) have erroneous beliefs about the condition, which in turn increases anxiety and depression. Providing information and facts about CHD through video may be able to correct the wrong conceptions of individuals about their disease. A total of 150 individuals with CHD at Hasan Sadikin Hospital, Bandung, Indonesia (male = 65%, female = 35%) were divided into a control group and two experimental groups, with a quasi-experimental before-after design. The participants completed the York Cardiac Beliefs questionnaire at the start of the measurement, immediately after watching the video (time 1), and again after watching the video six times over a two week period (time 2). Beck Anxiety Inventory and Beck Depression Inventory-II questionnaires were also completed by participants at the beginning of the experiment and at time 2. The repeated measures ANOVA analysis showed a significant decrease in both experimental groups in terms of wrong beliefs about CHD (t=8.68 & 8.69, p< .01), anxiety (p< .01), and depression (t=8.17 & 7.76, p< .01). Watching videos giving facts and information about CHD can therefore correct erroneous beliefs about CHD, and reduce levels of anxiety and depression in individuals suffering from the disease.